FOREIGN DIRECT INVESTMENT AND ENTRY MODES OF MOBILE TELECOMMUNICATION COMPANIES IN ALBANIA - Mukli, Lindita; Cota, Aurela; Mersini, Rezarta (European Scientific Journal, ESJ, 2012)
Foreign Direct Investment, namely, FDI, is a very important economic development factor in a country.As Albania attempts to access the EU, it is implementing policies to be an attractive country for FDI inflows. The purpose of this paper is to identify the determinants and patterns of FDI flows, the host country and the entry modes of foreign firms that have entered the Albanian Mobile Telecommunication Industry. In order to determine the main factors of FDI inflows in the telecommunications sector in Albania, FDI movements and activities of main Mobile Networks operating in the country, Vodafone Albania and Eagle Mobile, have been analysed. A general view of FDI situation in Albania, as well as advantages and disadvantages that a country faces in attracting foreign investors are described. This study offers a new perspective to the most crucial FDI determinants used in Mobile Telecommunications Industry in Albania. It benefits future research with new findings, by taking into consideration new market strategies and alternatives for entry choices.